Man vill skrika ut det över världen, jag kan lika gärna skriva det på Facebook. Ungdomar och vänskap on-line - Sivenbring, Jennie (Educare, 2016)
This article examines how a group of young people relates to interaction and friendship on Facebook. Using a theoretical framework based on the work of Erving Goffman, it draws upon a focus group interview and on netnographic observations of a private Facebook group and on the individual Facebook profiles of a group of young people. The results demonstrate how the participants use the social network as an arena for establishing and working on already existing relations. It is also argued that the different settings in the group and the individual profiles condition the way in which the young people interact and perform to manage the impressions given to differing audiences.